Komunikasi Kontroversial Tokoh Publik 2025: Perspektif Etika Komunikasi Islam dan Moderasi Beragama - Musyaffa; Juriana; Mutia Tanseba Andani; Nasrul Efendi; Agam Anantama (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2025)
This article analyzes controversial communication practices by several public figures in 2025, positioning Islamic communication ethics and religious moderation as the primary normative framework. The study employs critical discourse analysis combined with a literature review on Islamic communication ethics and religious moderation. Data are analyzed through public figures’ verbal statements, non-verbal expressions, and netizens’ responses as circulated in mass media and social media. The findings reveal that controversial communication by public figures, particularly legislative officials, is widely perceived as inconsistent with core principles of Islamic communication ethics, including qaulan ma'rufan, qaulan sadidan, and qaulan layyinan. This study emphasizes that internalizing Islamic communication ethics and religious moderation is essential for public communication to maintain social order, strengthen public trust, and prevent social unrest and potential disintegration.